Relationships between pyrimidine metabolism and sensitivity to alkylating agents in Aspergillus nidulans. - P. Hooley; S. G. Shawcross; P. Strike (Fungal Genetics Reports, 1987)
Relationships between pyrimidine metabolism and sensitivity to alkylating agents in Aspergillus nidulans.